Increasing the self-assessment level of adolescent children through interactive work forms - E. Yu. Eliseeva (Вестник университета)
In this article, the author conducts a comprehensive theoretical analysis of the possibilities of using interactive (dialogue) work forms in the context of increasing the self-esteem level of adolescent children. Mainly, the current activity areas of a teacher-psychologist with younger and older adolescents are analysed. The main advantages of the subject-subject work form are formed, as well as the potential opportunities for introducing modern information technologies into the work system on the self-esteem level of adolescents are given. Thus, the theoretical analysis results carried out allow us to note that interactive work forms provide colossal variant directions for the psychological and pedagogical diagnostic implementation and directly corrective activity aspects. Among other things, the key feature of their application is the ability to adapt the dialogue to the personal characteristics of each teenager, which increases the successful communication likelihood and further psychological and pedagogical support organisation.